Fall risk assessment in elderly with and without history of falls: gait electromyographic analysis: a comparative study - Coutinho, António (2014)
Objectives: To determinate if there were differences in electromyography parameters of rectus anterior, biceps femoris, gluteus medius, soleus, gastrocnemius medialis and tibialis anterior muscles between group with and without history of falls during. Was analized the relationship between the levels of muscle activation and score in POMA (Performance-Oriented Mobility Assessment). Materials and Methods: This is a transversal, not experimental and comparative study. The sample was composed by 30 older adults, 15 with and 15 without history of falls. To collect the data of electromyography was used BIOPAC systems and followed the SENIAM guidelines. For the collection of kinematic data was used Kinovea program and for assess the risk of falling was applied POMA. Results: Individuals with history of falls present levels of muscle activity relatively to maximum voluntary contraction (MVC) higher in the dominant lower limb (right) compared to subjects without a history of falls, however these differences aren´t statistically significant (p>0,05). There is enormous variation between the sample in relation to phases of gait in which the muscles are more actives. The group with history of falls shows values lower than group without history of falls in POMA score, the difference is significant (p=0.001). The relationship between percentage of muscle activation and the values obtained in POMA not proved statistically significant (p>0,05). Conclusion: Although results obtained weren´t statistically significants, we can conclude that individuals with falls have higher levels of muscle activation relative to MVC that individuals without history of falls, it is believed that the changes are related to the development of strategies for increased stability during gait. There is considerable variability in phases in which the subjects engaged higher levels of muscle activation, which might occur due to task compensatory strategies or by the task have been made at speed of comfort for the individual. It follows that POMA is an instrument more sensitive and effective to identify the risk of falling in these individuals that the electromyographic analysis.